СОПОСТАВИТЕЛЬНЫЙ АНАЛИЗ СУБСТАНТИВНЫХ ФРАЗЕОЛОГИЧЕСКИХ ЕДИНИЦ С КОМПОНЕНТОМ ЗООНИМОМ АНГЛИЙСКОГО И КАРАКАЛПАКСКОГО ЯЗЫКОВ - Сагатова Зарима (International Scientific and Current Research Conferences, 2023)
In modern scientific literature, a large number of studies are devoted to human observation of animals and the multifunctionality of images of representatives of the animal world. This article analyzes the semantic structure of English and Karakalpak substantive phraseological units with zoonym components. The above analysis showed that the semantic properties of the studied substantive phraseological units have a significant similarity. However, they differ in semantics of the zoonym component, which reflects the mentality of the people.